Cooperative path replanning method for multiple unmanned aerial vehicles with obstacle collision avoidance under timing constraints. (August 2015) - Zhen, Ziyang; Gao, Chen; Zheng, Fengying; Jiang, Ju
An online cooperative path replanning method based on the rapidly-exploring random tree (RRT) algorithm for multiple unmanned aerial vehicles (UAVs) is presented. Chaotic sequence is used to improve the RRT algorithm. The improved RRT is applied in online path replanning to round unexpected threats detected while flying along the pre-path, which is designed in advance and satisfies time cooperativity. Because time cooperativity is destroyed by path replanning, a time cooperativity reconstruction strategy is proposed, which is realized by adjusting the flight velocities associate with the circling motions so that all UAVs can reach the destination at the same time. Finally, the simulations are carried out to evaluate the effect of key parameters, and verify the effectiveness of the proposed cooperative path replanning method.